Work and the Nineteenth-Century Press Living Work for Living People - King, Andrew (Taylor & Francis, 2023)
Extending the limits of the award-winning Routledge Handbook to Nineteenth-Century Periodicals and Newspapers (2016) and its companion volume (and also award-winning) Researching the Nineteenth-Century Press: Case Studies (2017), Work and the Nineteenth-Century Press: Living Work for Living People advances our knowledge of how our identities have become inextricably defined by work. The collection's innovative focus on the nineteenth-century British press's relationship to work illuminates an area whose effects are still evident today but which has been almost totally neglected hitherto. Offering bold new interpretative frameworks and provocative methodologies in media history and literary studies developed by an exciting group of new and established talent, this volume seeks to set a new research agenda for nineteenth-century interdisciplinary studies.